CHILDREN’S DIGNITY IN MUSIC EDUCATION AND LOCAL COMMUNITY IN RECENT JAPAN - Kubota, Keiichi (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
This paper explores the role of music education in upholding children’s dignity within the context of Japan's evolving demographic and multicultural landscape. Japan faces a rapid population decline, prompting an increased reliance on foreign workers and their families. This demographic shift introduces challenges for children of foreign descent who often navigate between their native language and Japanese in educational settings. The paper examines the ethical responsibilities of music educators in fostering inclusivity and addressing cultural dilemmas. It emphasizes that music, as a social and ethical practice, significantly influences children's psychological, social, and intellectual development. The discussion highlights the need for curricula that respect diverse linguistic and cultural backgrounds, proposing innovative approaches such as intercultural music workshops. These workshops enable foreign and Japanese children to engage in mutual learning by sharing traditional songs from various countries. The paper also underscores the importance of community-based initiatives and crowdfunding in supporting such educational endeavors. By prioritizing the dignity and holistic development of all children, this study advocates for a transformative approach to music education that reflects the values of a multicultural society. The findings contribute to global discussions on inclusive education and the ethical responsibilities of educators in diverse communities.